Sundance: hangman's knot - McCurtin, Peter (Lindford, 1989)
Sundance's order came straight from General George Crook: Escort the hated Apache war chief Geronimo to what Crook decided would be Geronimo's new home in the Indian Territory of Oklahoma. It should have been an easy assignment, but Geronimo escaped and Sundance found himself stranded in a shack, surrounded by gunfire, with nothing but a five-shot revolver between him and a shallow grave.Josiah Moore's ruthless and well-armed hunting expedition had invaded the Staked Plains to kill off the last of the buffalo herds. But their presence on Indian land threatened to cause an all-out war. Desperate, General Crook called in Sundance and told him the only way to avoid a massacre was to drive Moore and his men off the Plains -- something easier said than done.
59763
Keywords: Large Print